Transcatheter technique now standard for Secundum ASD Closure, A case report of our first experience - Reza, AQM; Siddique, AB; Talukder, MSU; Munwar, S; Islam, AHM W; Sohel, SR; Ghani, MA (Pulse, 2011)
DOI: http://dx.doi.org/10.3329/pulse.v4i1.6963 Pulse Vol.4 January 2010 p.32-33